2021
DOI: 10.3390/cancers13040855
|View full text |Cite
|
Sign up to set email alerts
|

The Radiation-Induced Regenerative Response of Adult Tissue-Specific Stem Cells: Models and Signaling Pathways

Abstract: Radiotherapy is involved in the treatment of many cancers, but damage induced to the surrounding normal tissue is often inevitable. Evidence suggests that the maintenance of homeostasis and regeneration of the normal tissue is driven by specific adult tissue stem/progenitor cells. These tasks involve the input from several signaling pathways. Irradiation also targets these stem/progenitor cells, triggering a cellular response aimed at achieving tissue regeneration. Here we discuss the currently used in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…− 53 In this study, we demonstrate that the loss of Cldn7 led to disruption in the large intestine crypt stem cell population, which resulted from decreased Lgr5‐positive active stem cells accompanied by an increase in quiescent and transit‐amplifying cells. Epithelial hyperproliferation seen with in vivo Cldn7 KO is likely a compensatory effect of the loss of the stem cell population, comparable to colonic stem cell damage‐induced hyperproliferation seen with radiation 54 . Without claudin‐7, crypt cells were unable to survive and form colonoids with differentiated epithelial cells in culture, highlighting the vital role of claudin‐7 in IESC survival and differentiation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…− 53 In this study, we demonstrate that the loss of Cldn7 led to disruption in the large intestine crypt stem cell population, which resulted from decreased Lgr5‐positive active stem cells accompanied by an increase in quiescent and transit‐amplifying cells. Epithelial hyperproliferation seen with in vivo Cldn7 KO is likely a compensatory effect of the loss of the stem cell population, comparable to colonic stem cell damage‐induced hyperproliferation seen with radiation 54 . Without claudin‐7, crypt cells were unable to survive and form colonoids with differentiated epithelial cells in culture, highlighting the vital role of claudin‐7 in IESC survival and differentiation.…”
Section: Discussionmentioning
confidence: 92%
“…Epithelial hyperproliferation seen with in vivo Cldn7 KO is likely a compensatory effect of the loss of the stem cell population, comparable to colonic stem cell damage-induced hyperproliferation seen with radiation. 54 Without claudin-7, crypt cells were unable to survive and form colonoids with differentiated epithelial cells in culture, highlighting the vital role of claudin-7 in IESC survival and differentiation. Nearly 50% of patients with CRC exhibit chemoresistance and tumor recurrence involving colon cancer stem cells (CSCs).…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with enhanced radiosensitivity of the gut and bone marrow in ATM -deficient mice ( 59 , 60 ). Asymmetric division of stem cells after radiation is responsible for restoring tissue homeostasis, and the profound sensitization of oral mucosa by AZD1390 likely reflects sensitization of the stem cell compartment ( 61 ). These results contrast with protection against radiation-induced neuronal apoptosis in juvenile ATM -null mice ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient #2’s CRLM PDOs demonstrated high levels of the stem cell marker Lgr5 following treatment with captopril and this may indicate resistance to radiotherapy. Studies have shown that although Lgr5+ stem cells in the intestine appear highly sensitive to radiation therapy, those in the colon are not [ 54 , 55 ]. This could inform treatment decisions away from therapies such as SIRT or SBRT and towards other therapies, such as microwave ablation, targeted chemotherapies, or monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%